2018
DOI: 10.1002/aur.1955
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physical activity interventions on youth with autism spectrum disorder: A meta‐analysis

Abstract: Results of the meta-analysis-a method for synthesizing research-showed physical activity interventions to have a moderate or large effect on a variety of outcomes, including for the development of manipulative skills, locomotor skills, skill-related fitness, social functioning, and muscular strength and endurance. The authors conclude that physical activity's standing as an evidence-based strategy for youth with ASD is reinforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 92 publications
(77 reference statements)
8
108
2
7
Order By: Relevance
“…Basic information from recent studies about exercise intervention in patients with autism is shown in Table 4. Overall, exercise intervention appears to benefit the development of physical health and social communication skills, including operating skills, motor skills, muscle strength, and endurance for youth with autism (Healy et al, 2018). These studies establish that exercise intervention may be a feasible treatment for autism.…”
Section: Effects Of Exercise Intervention On Autismmentioning
confidence: 72%
“…Basic information from recent studies about exercise intervention in patients with autism is shown in Table 4. Overall, exercise intervention appears to benefit the development of physical health and social communication skills, including operating skills, motor skills, muscle strength, and endurance for youth with autism (Healy et al, 2018). These studies establish that exercise intervention may be a feasible treatment for autism.…”
Section: Effects Of Exercise Intervention On Autismmentioning
confidence: 72%
“…This approach calculates the effect size if each of the studies in the meta‐analysis were individually removed. In this way, the influence of any given study can be noted if its removal leads to a substantial change in the overall effect size (i.e., the effect size with the study removed was not within the confidence intervals; see Healy, Nacario, Braithwaite, & Hopper, in press, for a similar approach). As shown in Data S2 (Table B1), the removal of any one of the studies would not substantially change the results of the meta‐analysis on reading performance.…”
Section: Rq1: Reading Performance Results and Discussionmentioning
confidence: 99%
“…This indicates younger age groups provide a critical window of opportunity to promote good health outcomes through participation in PA programs. PA's effectiveness has been demonstrated in children with physical disabilities such as cerebral palsy (CP) [6], genetic conditions such as Down syndrome (DS) [7] and neurodevelopmental conditions such as autism spectrum disorder (ASD) [8]. Benefits have been shown to span motoric [9], and aspects of cognitive [10] and socio-emotional domains [11] among disability populations.…”
Section: Introductionmentioning
confidence: 99%